MEASUREMENT AND ANALYSIS OF I-V-T CHARACTERISTICS OF A AUGENI/P-SI SCHOTTKY BARRIER DIODE - TERGHINI, W.; SAADOUNE, A.; DEHIMI, L.; MEGHERBI, M.L.; ÖZÇELIKC, S. (Courrier du Savoir, 2015)
ABSTRACT In this work, we report measured forward current voltage characteristics of AuGeNi/p-Si schottky barrier diode in the temperature range of 295-400 °K. Forward current voltage characteristics were investigated. This investigation is based on the analysis of the dependency of extracted parameters such as ideality factor (η), barrier height ( ) and saturation current ( ) on temperature. The Richardson coefficient was examined by means of the saturation versus temperature. While η decreases, ØB0 increases with increasing temperature. Obtained Richardson constant value of the A*=11.5 x10-7Acm-2K-2 is very low compared to the standard value. The modified Richardson plot has given mean barrier height and Richardson constant (A*) as 1.15 eV and 30.53 Am-2K-2, respectively. The temperature dependence of the I–V characteristics of the AuGeNi/p-Si Schottky diode have been successfully explained on the basis of thermionic emission (TE) mechanism with Gaussian distribution of the Schottky barrier heights (SBHs). KEYWORDS: Schottky contacts, current-voltage-temperature characteristics, Gaussian distribution, Barrier inhomogeneity.